we are given the following functions:
![\begin{gathered} f(x)=6x+3 \\ g(x)=x-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1hvcemfjl5iz8aahhb2jf9ctcmb3v5kblb.png)
We are asked to determine:
![(f+g)(3)](https://img.qammunity.org/2023/formulas/mathematics/college/tfruldmsf9k6i2e0yb5l1b7ai6x7bxlbxd.png)
To do that, let's remember the following relationship:
![(f+g)(3)=f(3)+g(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/z6w9ihbfqs3sgyp4nf59rj6cyzorspuwt8.png)
Therefore, we need to substitute x = 3 in each function. Substituting in f(x):
![\begin{gathered} f(3)=6(3)+3 \\ f(3)=18+3 \\ f(3)=21 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/l8amdeozg9cyfddo8s2fvzuha84eczz1tx.png)
Substituting in g(x):
![\begin{gathered} g(3)=3-7 \\ g(3)=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5rvj6mbmwovdc0p67foshwitlg4u0ch909.png)
Adding both functions:
![f(3)+g(3)=21-4=17](https://img.qammunity.org/2023/formulas/mathematics/high-school/egx4fy6eqrwzkectle3avizwvz1k2xaoyc.png)
Therefore, the answer is 17.